Tropane alkaloids and the potential for accidental or non-accidental mass outbreaks of anti-cholinergic toxidrome - David Heslop (University of New South Wales, 2023)
In December 2022 a large outbreak of anti-cholinergic toxidrome was reported in Australia associated with contamination of baby spinach leaves with Datura stramonium. Over 100 individuals around Australia experienced symptoms consistent with intoxication with the primary plant derived tropane alkaloids scopolamine, hyoscyamine and atropine. Tropane alkaloids are part of a wider group of incapacitating chemical substances that includes the chemical weapon BZ that results in the characteristic anti-cholinergic toxidrome. Human food production and manufacturing processes are prone to accidental and non-accidental contamination with tropane alkaloids, and food quality standards and measures are essential to protecting food security where incorporation of tropane alkaloids is possible. While mass non-accidental contamination of human food production and manufacture is a possibility, historically exposure scenarios involving tropane alkaloids have usually been limited to small scale poisoning events dating back to antiquity. This article summarises the risks of accidental and non-accidental exposure to tropane alkaloids with particular focus on the potential for mass exposure events.